Socialization of the Making of Learning Comic Media Using the Make Beliefs Comix Website at SDN Bukur - Rahmat Setyo Jadmiko; Nourma Oktaviarini; Eka Yuliana Sari; Janattaka, Nugrananda (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2021)
This sosialization aims to optimize limited face-to-face learning by using comic learning media through the Make Beliefs Comix website’s. The core activity is in the form of socialization activities about making learning media that attract students' attention by displaying comics according to the learning theme. This activity was carried out twice in August, prinecisely in the first week. At the beginning meeting the teacher was introduced to the Make Beliefs Comix media and tutorials for its use, while in the last meeting , the teacher presented the comics that had been made. The result of socialization can make teacher to produce commix according to themes how this teach in classroom, and make interactive story in commix strips in according situation in class and learning material.